2008
DOI: 10.3892/ijo.32.2.317
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination strategy to target lysyl oxidase-like 4 in dendritic cell based immunotherapy for head and neck cancer

Abstract: Abstract. Overexpression of lysyl oxidase (LOX) is associated with the invasive potential of metastatic breast and head and neck cancer (HNC) cells and reduced metastasis-free and overall survival. Recently, we have demonstrated up-regulation of a new member of the LOX family, lysyl oxidase-like 4 (LOXL4), in invasive HNC revealed a significant correlation between LOXL4 expression and local lymph node metastases and higher tumour stages. The objective of this study was to examine whether cellular LOXL4 may pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…We have found selective upregulation and amplification of the LOXL4 gene, overexpression of LOXL4 protein in primary and metastatic HNSCC cell lines and in patients with invasive HNSCC which correlated with local lymph node metastases versus primary tumor types and higher tumor stages . We also developed an affinity purified polyclonal antibody raised against the 85 kD LOXL4 antigen to demonstrate its expression in HNSCC tissues of different grading and staging, and studied its involvement in the structural organisation of squamous epithelia . So far, most of the described antibodies against HNSCC showed considerable cross reactivity with normal tissue or showed only reactivity with SCC of distinct sites of origin .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have found selective upregulation and amplification of the LOXL4 gene, overexpression of LOXL4 protein in primary and metastatic HNSCC cell lines and in patients with invasive HNSCC which correlated with local lymph node metastases versus primary tumor types and higher tumor stages . We also developed an affinity purified polyclonal antibody raised against the 85 kD LOXL4 antigen to demonstrate its expression in HNSCC tissues of different grading and staging, and studied its involvement in the structural organisation of squamous epithelia . So far, most of the described antibodies against HNSCC showed considerable cross reactivity with normal tissue or showed only reactivity with SCC of distinct sites of origin .…”
mentioning
confidence: 99%
“…16,17 We also developed an affinity purified polyclonal antibody raised against the 85 kD LOXL4 antigen to demonstrate its expression in HNSCC tissues of different grading and staging, and studied its involvement in the structural organisation of squamous epithelia. 18 So far, most of the described antibodies against HNSCC [19][20][21][22][23][24][25] showed considerable cross reactivity with normal tissue or showed only reactivity with SCC of distinct sites of origin. 26 The first successful radioimmunotherapy results for HNSCC were shown with the E48 mAb in the early 1990 sec.…”
mentioning
confidence: 99%
“…Peptides and PLGA polymer HLA-A*0201 restricted peptides of Mart-1 [27][28][29][30][31][32][33][34][35] (Mart-1, AAGIGILTV), 16 Survivin 95-104 (SV95, ELTLGEFLKL) 17 were synthesized by GenScript Corporation (Piscataway, NJ). The purity and identity of the peptides were determined using HPLC analysis and mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro controlled release of peptide was completed as we previously described with minor modification. 18 Mart-1 [27][28][29][30][31][32][33][34][35] or Survivin 95-104 peptide-loaded PLGA-NPs aliquots were suspended in PBS (pH 7Á4) containing 0Á01% sodium azide, and the suspension was incubated at 37°in a shaking incubator (60 r.p.m.). Triplicates were set up for each time-point.…”
Section: Study Of In Vitro Sustained Peptide Releasementioning
confidence: 99%
“…However, the growth of existing metastases was not affected (67). In a feasibility study, we transfected cloned LOXL4-mRNA into immature dendritic cells and showed that cellular expression of LOXL4 could provide an effective target for cell mediated immunotherapy (68). Another important aspect of metastasis formation is the phenomenon of directional movement, which is well characterized for many cells, particularly leukocytes.…”
Section: Tissue Invasion and Metastasismentioning
confidence: 99%